The Fuel Problem in Bombay State - Kaikini, N. S.; Mokashi, V. K. (Indian Forester, 1956)
The fuel problem in the Bombay State is covered with special emphasis on the wasteful use of Cowdung as fuel. Statistical data about the quantity of Cowdung used as fuel and how it could be made to provide manure for the fields, especially on bunds is recommended and its value assessed. Village woodlands and farm wood lots are also suggested to supplement the fuel resources.